THE TEMPORAL CITY AND THE UNFOLDING URBAN EVOLUTION THROUGH TIME AND SPACE - Dilshod Khaydarov (The Conference Hub, 2025)
This article explores the concept of “temporal cities” by examining the transformation of urban centers over time. Through historical, economic, cultural, and environmental lenses, the study highlights how cities evolve in response to technological innovations, demographic shifts, and global trends. Using a multidisciplinary approach, this paper analyzes the characteristics of temporal cities and proposes frameworks to understand their current functions and future trajectories.
Keywords: temporal cities, urban transformation, modern urbanization, city evolution, urban dynamics, sustainable cities, historical urban development